The monstrous feminine : media representations of women who commit crime in New Zealand : a thesis presented in partial fulfilment for the degree of Master of Arts in Psychology, Massey University, Albany, New Zealand - Mackie, Emma (Massey University, 2016)
Women who have committed crime appear to be portrayed by the media as sick, deviant and/or dangerous and positioned as the monstrous feminine, deviant from natural womanhood. Several syndromes and disorders have been created by the psychological community to explain the ‘abnormal’ behaviour of these women. The New Zealand media engages in the use of stereotypes to frame their stories to position women within these specific discourses which are legitimized by the ‘experts’. This research aims to understand how women who commit crime are represented in the media and how the discourses that maintain the underlying structures of power in society are produced and reproduced through the continuous retelling of a particular narrative that maintains gendered social power relations. This research seeks to understand how media representations of women who have committed a crime are reproduced through discourses of sexual difference. Discourses were analysed using Foucauldian Discourse Analysis to unpack the relationship between psychological knowledge of women’s deficit and media representations of madness. The analysis of 39 articles determined the discourses of women’s madness and badness were common when discussing the reasons for women’s criminal activity. The discourses of madness are based on highly gendered assumptions of what constitutes hegemonic femininity. These discourses are legitimised by the DSM and have become common knowledge via the media. The monstrous feminine is applied to those women who exhibit socially deviant behaviour unacceptable for women and those seen as responsible for the destruction of traditional societal values and going against women’s ‘natural’ maternal instincts. Analysis concluded the discourse of badness is enacted when women cannot be positioned as mad to explain her unfeminine behaviour. ‘Badness’ is apparent when discussing mothers who commit crime. These mothers are positioned as having deviated from the motherhood mandate by not conforming to the moral trajectory of the ‘good’ mother. By merely positioning women as mad or bad because of their failure to conform to traditional gender norms, we are missing the opportunity to help women and address the issues within their lives that led to committing a crime. Without understanding the conditions of women’s lives, the context of women’s offending continues to be rendered invisible, and leaves little opportunity for intervention. The assumptions that inform the construction of the discourses of madness need to be challenged so that women’s criminal behaviour is not masked by assumptions of a deficit biology, and her distress is not pathologised.
Keywords: Female offenders; Crime in mass media; New Zealand; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Psychology